Use of rRNA fluorescence in situ hybridization for measuring the activity of single cells in young and established biofilms. - Poulsen, L K (1993)
We describe the in situ use of rRNA-targeted fluorescent hybridization probes in combination with digital microscopy to quantify the cellular content of ribosomes in relationship to the growth rate of single cells of a specific population of sulfate-reducing bacteria in multispecies anaerobic biofilms. Using this technique, we inferred that this population was growing with an average generation time of 35 h in a young biofilm, whereas the doubling time in an established biofilm was significantly longer. Conventional chemical determinations of the RNA, DNA, and protein contents of this culture at different growth rates were also carried out, and the resulting data were compared with the rRNA fluorescence in situ hybridization data.